The Effect of Health Insurance on Child Nutritional Outcomes. Evidence from a Regression Discontinuity Design in Peru - Noelia Bernal; Joan Costa-Font; Patricia Ritter (Institute of Labor Economics (IZA), 2022)
We study the effect of health insurance expansion on nutrition-related children's health outcomes. We exploit quasi-random variation from an insurance expansion targeted at poor households in Peru. We find that access to insurance reduces childhood obesity and exerts positive and economically significant effects on some preventive health care utilization and behaviours, such as children's regular growth checks-ups and deworming treatments, the duration of breastfeeding, and a substitution of foods rich in carbohydrates for other foods rich in proteins. In contrast, we do not find any effect on other outcomes typically related to other interventions.
Keywords: I18; J13; 330; children's health; obesity; overweight; public health insurance; health behaviors; nutrition; breast-feeding